2016
DOI: 10.1093/femsle/fnw062
|View full text |Cite|
|
Sign up to set email alerts
|

ATF3 provides protection fromStaphylococcus aureusandListeria monocytogenesinfections

Abstract: Activating transcription factor 3 (ATF3) is a stress-induced transcriptional regulator in eukaryote. The role of ATF3 in cancer has been well defined, but how ATF3 functions in bacterial infection is not well understood. Pneumococcal infection has been shown to induce ATF3 expression, which subsequently enhances cytokine production and provides protection from lethal Streptococcus pneumoniae infection, but the role of ATF3 in other Gram-positive (G(+)) infections remains unclear. Here, we report that infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…This phenomenon either blocks NLRP3 priming or promotes cell death (35, 36). In a previous study, we identified different reactions in cytokinesis dependent on whether infection was caused by gram-positive or -negative bacteria (9). Consistent with cytokines, ATF3 KO BMDMs exhibited increased ROS production after infection with either gram-positive or gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon either blocks NLRP3 priming or promotes cell death (35, 36). In a previous study, we identified different reactions in cytokinesis dependent on whether infection was caused by gram-positive or -negative bacteria (9). Consistent with cytokines, ATF3 KO BMDMs exhibited increased ROS production after infection with either gram-positive or gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, ATF3 is believed to moderate ROS levels rather than to serve as an unconditional negative regulator in gram-negative bacteria. Thus, it was presumed that the similar ROS levels observed during infection with gram-positive bacteria in ATF3 KO mice resulted from defects in ROS inhibition and cytokine production, and thus failed to defend against E. coli through an inability to produce sufficient cytokines (9). In the case of gram-negative bacteria, inflammasome activation elicits IL-1β production via a complicated mechanism (37, 38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATF3 dampens the TLR4mediated macrophage inflammatory response to LPS (Gilchrist et al, 2006;Hoetzenecker et al, 2011), and inhibits IL-6 expression in Neisseria gonorrhoeae-infected T84 human colorectal cells (Calton, Wade, & So, 2013), or in uropathogenic Escherichia coli-infected cells (Nguyen et al, 2016). In order to develop such strategies, understanding the response of the host to the bacterium is a prerequisite.…”
Section: Discussionmentioning
confidence: 99%
“…During Streptococcus pneumoniae infection, ATF3 positively regulates the production of cytokines such as tumour necrosis factor (TNF)-α, IL-1β, and IFN-γ and ATF3-knockout mice are more susceptible to S. pneumoniae infection than their wildtype counterparts (Nguyen, Kim, Luong, Pyo, & Rhee, 2014;Nguyen et al, 2016). During Streptococcus pneumoniae infection, ATF3 positively regulates the production of cytokines such as tumour necrosis factor (TNF)-α, IL-1β, and IFN-γ and ATF3-knockout mice are more susceptible to S. pneumoniae infection than their wildtype counterparts (Nguyen, Kim, Luong, Pyo, & Rhee, 2014;Nguyen et al, 2016).…”
mentioning
confidence: 99%